Ti3+ doped anodic single-wall TiO2 nanotubes as highly efficient photocatalyst - Motola, Martin; Čaplovičová, Mária; Krbal, Miloš; Sopha, Hanna; Thirunavukkarasu, Guru Karthikeyan; Gregor, Maroš; Plesch, Gustav; Macák, Jan (Elsevier, 2019)
In this work, a two-step treatment of TiO2 nanotube (TNT) layers towards enhanced photocatalytic performance is presented. TNT layers with a thickness of ~7 µm and an average inner diameter of ~190 nm were prepared via electrochemical anodization of Ti foil in a fluoride containing ethylene glycol-based electrolyte. To improve the photocatalytic activity of the produced TNT layers a two-step post-treatment was conducted. First, the inner shell of the native double-wall TNT layers was removed via a mild pre-annealing followed by a selective etching treatment of the inner shell in piranha solution yielding single-wall TNT layers. Second, reduction via annealing in H2/Ar atmosphere was performed. The resulting Ti3+ doped single-wall TNT layers possess 100% enhancement of photocatalytic activity compared to their non-treated counterparts.
Keywords: TiO2 nanotube layers; single-wall; H2 surface reduction; photoelectrochemistry; photocatalysis